Non-Occlusive Mesenteric Ischemia in Children With Diabetic Ketoacidosis: Case Report and Review of Literature - Frontino, Giulio; Di Tonno, Raffaella; Castorani, Valeria; Rigamonti, Andrea; Morotti, Elisa; Sandullo, Federica; Scialabba, Francesco; Arrigoni, Francesca; Foglino, Riccardo; Dionisi, Benedetta; Ferri, Chiara Irene Carla; Zirpoli, Salvatore; et al. (Frontiers in Endocrinology, 2022)
Introduction: Despite the use of technology, recurrent diabetic ketoacidosis (DKA) prevention remains an unmet need in children and adolescents with T1D, and may be accompanied by life-threatening acute complications. We present a rare case of non-occlusive mesenteric ischemia (NOMI) with overt manifestion after DKA resolution and a discussion of recent literature addressing DKA-associated NOMI epidemiology and pathogenesis in children and adolescents. Case Presentation: A 13-year-old female with previously diagnosed T1D, was admitted at our emergency department with hypovolemic shock, DKA, hyperosmolar state and acute kidney injury. Mildly progressive abdominal pain persisted after DKA correction and after repeated ultrasound evaluations ultimately suspect for intestinal perforation, an intraoperative diagnosis of NOMI was made. Conclusion: The diagnosis of DKA-associated NOMI must be suspected in pediatric patients with DKA, persistent abdominal pain, and severe dehydration even after DKA resolution.